The effect of microflocculant MBFA9 and the mechanism of Pb(II) and Zn(II) removal from an aqueous solution. Issue 5 (July 2019) - Zhang, Jiaqi; Jiang, Binhui; Zhang, Bo; Li, Yu; Fang and, Ping; Hu, Xiaomin
The removal mechanism of a microbial flocculant produced using a novel Paenibacillus sp. strain A9 (MBFA9) for two heavy metal ions, lead and zinc, from an aqueous solution is studied and compared. The removal rate of Pb(II) or Zn(II) by MBFA9 increased with an increase in the pH when the pH was less than 6.0. The removal rates were 91.26% for Pb(II) and 76.28% for Zn(II). The optimum condition was found at a pH of 5.5 and dosage of MBFA9 of 5% (v/v, 150 mg/L). When the initial concentration of metal ions was 100 mg/L, the removal capacity was 453.70 mg/g for Pb(II) and 398.48 mg/g for Zn(II). The capture process of a single metal ion of Pb(II) or Zn(II) by MBFA9 agreed with the Langmuir adsorption model with fitting coefficients of 0.9907 and 0.9408, respectively. Both the adsorption kinetics and adsorption equilibrium, usually described as adsorption isotherms, showed that this process of Pb(II) or Zn(II) capture by MBFA9 involved simple adsorption of a single molecular layer. The maximum reaction rate constant, K 2, of MBFA9 in the captured Pb(II) decreased from 0.0497 to 0.0095, with an increase in the Zn(II) concentration under different Zn(II) concentrations (0, 20, and 40 mg/L). This indicated that the presence of Zn(II) competed with PB(II) for the binding sites of MBFA9 and led to a decrease in the removal rate. The process was controlled by chemical adsorption.